Childhood vulnerabilities in South Africa: some ethical perspectives - Grobbelaar, Jan; Jones, Chris (Sun Press, 2020)
The plight and vulnerability of children living in South Africa and calling of the church -- Seen but not heard? Engaging the mechanisms of faith to end violence against children -- The contentious issue of corporal punishment in South Africa -- Reconceiving child theology from a queer theological perspective: for LGBTIQ+ parented families and children -- The stigmatisation of children living with FASD and their biological mothers -- Male initiation and circumcision - A South African perspective -- Recognising and responding to complex dilemmas: Child marriage in South Africa -- Children and racism -- Reflections on the effectiveness of child support grants -- Protecting children in the digital society